Effect of increasing GleptoForte dosage in newborn pigs on sow and litter performance - Hall, Brandon; Williams, Hayden E.; Jones, Cassandra K.; DeRouchey, Joel M.; Woodworth, Jason C.; Tokach, Michael D.; Dritz, Steven S.; Goodband, Robert D.; Holtcamp, A. (My University, 2017)
Gleptoforte, another iron complex that contains gleptoferron, may be an effective source of injectable Fe to treat anemia in young pigs. However, little data is available that confirms the appropriate level of iron injection needed to satisfy their requirement. Therefore, the objective of this experiment was to evaluate the effects of increasing dosage of Gleptoforte in newborn pigs on sow and litter performance. 28 litters totaling 336 newborn pigs (DNA 241 × 600, initially 3.83 ± 0.114 lb BW) were used in a 21-d farrowing study evaluating the effects of increasing Gleptoforte dosage on suckling pig performance and blood parameters. On the day of processing (d 3), piglets were weighed and six barrows and six gilts per litter were allotted to treatment in a completely randomized design for a total of 56 pigs per treatment. Treatments consisted of 1) a negative control receiving no iron injection; 2) 50 mg of iron; 3) 100 mg of iron; 4) 150 mg of iron; 5) 200 mg of iron; 6) 200 mg of iron plus a 100 mg booster at d 11 of farrowing. Piglets were weighed at processing, d 11, and at weaning (d 21) to calculate ADG. Blood samples were collected via jugular venipuncture from one barrow per treatment from each litter on d 3, d 11, and d 21. Criteria measured included: Hemoglobin (Hgb), Hematocrit (Hct), Serum Fe, and Total Iron Binding Capacity (TIBC). ADG and ending BW improved (quadratic; P=0.001) with increasing dosage of Gelptoforte. However, no evidence of difference in performance in all three periods between the 200 mg and 200 mg + 100 mg of Gleptoforte was observed, which suggests the booster injection of 100 mg iron at d 11 did not yield additional benefits compared to the pigs that received only the 200 mg at d 3. There was no evidence of difference observed for any hematological criteria measured on d 3 prior to the iron injection. Hgb, and Hct increased (quadratic; P=0.001) with increasing dosage. Serum Fe and TIBC had varying results and did have a direct effect with increasing Gleptoforte dosage. In summary, no iron injection resulted in the poorest growth and blood parameters. Administering 100mg Gleptoforte resulted in the greatest growth performance. Administrating 200mg + 100mg Gleptoforte improved hematological criteria but did not influence piglet growth performance compared to 200mg.
Keywords: Fall 2017